Automated Stress Detection Using Non Invasive Parameters and Internet of Things - Balaji, Anithakrithi; Kumar M, Yaswanth; B, Aparna; Varshini Karthik, Dr (International Journal of Engineering and Technology, 2018)
Stress is an increasing cause of concern in today's world that manifests psychological and physiological complications. The study is focused at developing a low cost non invasive continuous stress monitoring prototype with an integrated infrared therapy application. Infrared light has considerable effect in lowering the cortisol levels and this property makes it a useful application in stress therapy. The Pulse rate and Galvanic Skin Response (GSR) sensors are used to detect the stress threshold of an individual through a wearable device. The sensor values from the body are given as a feedback to the device, to wirelessly activate a compact Infrared light therapy setup to the patient, when a programmable threshold value of the sensors is reached. The monitored sensor values are continuously updated on the Internet and the physician is notified in case of any abnormal stress levels through Internet of Things (IoT). A pilot study was conducted with 40 normal subjects to observe the changes in Pulse rate and GSR during relaxed and stressed states. By taking average, the stress threshold was identified to be different for different individuals. Thus the prototype is customizable for every individual based on their stress threshold that is easily programmable. The prototype is light weight, portable, battery operated and comfortable for use at home or work.Â Â
Keywords: stress; galvanic skin response; pulse rate; infrared